Análise institucional da concessão de benefícios fiscais como política de desenvolvimento do estado do Tocantins de 1999 a 2012 - Araújo, Maria Rosicleide do Nascimento (Universidade Federal do Tocantins, 2016)
The objective of this work was to analyze the perspective of economic neo-institutionalism, the institutional arrangement in which the Tocantins policy of granting tax benefits, was structured between the years 1999-2012, and to what extent that government policy has affected the economic performance State. For this, we used the quantitative and qualitative research with statistical analysis and content tools. The main results of the quantitative analysis demonstrates the principle that larger interstate trade flows are with Tocantins state in the Southeast Region, with specific in Sao Paulo. Regarding the variables related to the Agroindustrial Complex sectors, Wholesale and Proindústria, the best performances of the average growth rates for the period of government occurred, in general, the PG-4. In economic segments of Wholesale Trade, the exception was in respect to the collection of ICMS-TO and generation of formal jobs, while the best results occurred in the PG-3 and PG-2 respectively. In the Proindústria, the exception was only for the generation of formal jobs variable, whose period that got better rates was the PG-2. The period of government whose average growth rates of the variables analyzed were usually the worst performance was the PG-3. As for the effectiveness index of benefits granted by Tocantins, it was found that the best predictors were observed in PG-4 for Wholesale and Proindústria programs, and PG-2 for Agroindustrial Complex. The main results arising qualitative content analysis showed that the most effective government strategy to attract businesses to the state currently, is to grant tax incentives, which are also considered as the main reason for choosing a company to install or enlarge a project in Tocantins. Furthermore, the degree of institutionalization of policy incentives in the State, is considered unsatisfactory, given the various questions and doubts about him. What about state and national institutional changes, and future prospects, the understanding is that if the state knows overcome their barriers and bottlenecks, with defined strategies and invest in the development of their potential, the tendency is to create a favorable environment for companies. Thus, the changes that perhaps they do occur, have less harmful impacts to the economy Tocantins.